Application of Android-Based Mobile Learning Material on Planetary Motion - Prayogi, Rommy; Yunus, Erniati (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
This type of research is learning media development research. Learning media development is carried out in several stages, starting from analyzing student needs and character, formulating learning objectives, formulating material points, compiling evaluation instruments, compiling media scripts/drafts, carrying out expert validation, conducting trials and revisions. The subjects of this research were media expert validators and material experts as well as class XI MIA students at senior high school 6 Batanghari. The instruments in this research were an expert validation questionnaire and a questionnaire on student responses or perceptions of the resulting learning media. The results of this development research are physics M-Learning learning media on mobile phones with the Android operating system using Adobe Flash Professional CS6 software. This media was declared feasible by media expert validators and material experts. The results of feasibility testing based on student perceptions in class XI MIA senior high school 6 Batanghari obtained a media feasibility percentage of 86.25% (good). The feasibility aspect is seen from the aspect of the learning media product and the aspect of the material packaged in the media. These results indicate that the media produced is good and suitable for use in the physics learning process.